2000
DOI: 10.1002/(sici)1521-3765(20000303)6:5<869::aid-chem869>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Interactions of a Specialized Antibody with Cholesterol and Epicholesterol Monolayers

Abstract: The stereoselective recognition by monoclonal antibodies of two-dimensional monolayers of cholesterol spread at the air-water interface is presented. Using immunofluorescence, we show that one antibody, raised and selected against crystals of cholesterol monohydrate, specifically recognizes monolayers of cholesterol, but not monolayers of epicholesterol--its epimeric form. This demonstrates that stereoselective recognition also applies to protein-surface interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…In contrast, the CDC Thr-Leu pair must recognize specific features of cholesterol at or near the membrane surface to initiate the cholesterol-dependent interaction of the CDC with the cell. Previous studies have demonstrated that the 3-hydroxy headgroup of cholesterol in the 3-β stereoisomer configuration is required for recognition by the CDCs as well as a structurally intact A ring and iso-octyl hydrocarbon chain at C17 (30)(31)(32)(33). Cholesterol is a planar molecule that packs parallel to the phospholipid acyl chains and adopts a nearly perpendicular orientation to the cell surface (34), with the 3-β-hydroxy group at the surface and the iso-octyl chain near the bilayer core.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the CDC Thr-Leu pair must recognize specific features of cholesterol at or near the membrane surface to initiate the cholesterol-dependent interaction of the CDC with the cell. Previous studies have demonstrated that the 3-hydroxy headgroup of cholesterol in the 3-β stereoisomer configuration is required for recognition by the CDCs as well as a structurally intact A ring and iso-octyl hydrocarbon chain at C17 (30)(31)(32)(33). Cholesterol is a planar molecule that packs parallel to the phospholipid acyl chains and adopts a nearly perpendicular orientation to the cell surface (34), with the 3-β-hydroxy group at the surface and the iso-octyl chain near the bilayer core.…”
Section: Discussionmentioning
confidence: 99%
“…[203±205] On the other hand, some mechanisms have been identified that enhance crystallization. [141] Currently discussed, especially for the case of atherosclerosis, are: * the heterogeneous nucleation of calcium phosphates on the membranes of dead cells that contain phospholipids (phosphate groups act as nucleators), [192,195] * nucleation by antibodies that are specific for cholesterol, [205,206] and * cellular action of osteoblast-like cells (so-called pericytes) within arteries that form bonelike tissue. [207] For the case of atherosclerosis, obviously a number of effects are responsible for the pathological calcification; these range from purely physicochemical effects (supersaturation) [141] over biologically induced nucleation to the biologically controlled deposition of calcium phosphates by specialized cells.…”
Section: Reviewsmentioning
confidence: 99%
“…The antibody that recognizes the face of cholesterol monohydrate crystals also recognizes cholesterol molecules in a monolayer at the air-water interface, while antibodies that are not specific to cholesterol crystals do not. Moreover, the same antibody does not interact with monolayers of epicholesterol, showing fine stereochemical/structural discrimination between arrays of isomeric steroids (34). The antibody affinity to the cholesterol monolayers is so high that labeling by the antibody is observed in equilibrium with a residual concentration in solution as low as 10 -11 M (35).…”
mentioning
confidence: 99%